The use of virtual reality technologies in the process of teaching a foreign language with the game method - Liliya R. Nurtdinova; Ilya A. Bogachev (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This paper addresses the issue of the appropriateness of using a game method of teaching foreign languages with the help of virtual reality. The means of virtual reality are increasingly being introduced into various spheres of our life, including the educational environment. In that context the authors of this paper explain what virtual reality is, and how its technologies allow optimizing all fields of human activity, including teaching foreign languages. The main possibilities of virtual reality in the educational process are listed in the paper. The analysis of the game method of teaching is also given with all its main points. At the end of the paper the authors come to the conclusion that the various means of virtual reality are an excellent addition to the game method of teaching. They give a chance to the student to immerse himself into the language environment, practice effectively and learn new material as quick as possible.